2000
DOI: 10.1002/clc.4960230508
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of coronary angiography with “tombstoning” electrocardiographic pattern in patients after acute myocardial infarction

Abstract: Background: It has been suggested that a specific pattern of electrocardiographic (ECG) changes following acute myocardial infarction (AMI), the so-called "tombstoning," predicts a poorer outcome, although the cause and associations of such changes are not known. To address the possible cause and implications, we correlated angiographic findings with tombstoning in patients following AMI. Methods:The study investigated 124 patients with AMI, whose ECGs were taken within 24 h of onset of symptoms and who subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 10 publications
2
10
0
Order By: Relevance
“…In this context, recent clinical evidence that "tombstoning" ECG pattern was more strongly associated with acute anterior than inferior infarction could be interpreted as supportive of our study results (13). However, it is probably the more extensive myocardial territory (i.e., AR) being supplied by the LAD than the particular anterior site that explains the huge S-T segment elevations.…”
Section: Variably Vulnerable Myocardial Areassupporting
confidence: 88%
See 1 more Smart Citation
“…In this context, recent clinical evidence that "tombstoning" ECG pattern was more strongly associated with acute anterior than inferior infarction could be interpreted as supportive of our study results (13). However, it is probably the more extensive myocardial territory (i.e., AR) being supplied by the LAD than the particular anterior site that explains the huge S-T segment elevations.…”
Section: Variably Vulnerable Myocardial Areassupporting
confidence: 88%
“…In humans, investigations on regional differences in myocardial ischemia have allowed little more than speculation that the territory of ischemia might be another determinant of IS. For example, during acute myocardial infarction, "tombstone" ECG S-T segment elevation is tightly associated with a large infarct in the LAD region, which could be explained by the large AR in this territory and/or sitespecific myocardial vulnerability to ischemia (13). Quantitative collateral flow index (CFI) measurements in 450 patients with stable CAD have documented lower values in the LAD than in the left circumflex (LCX) and right coronary artery (RCA) regions (15).…”
mentioning
confidence: 99%
“…Tomb‐ST is not an infrequent event; it is detected among 25%–30% of STEMI patients (Guo, Yap, Chen, Huang, & Camm, ; Tomcsányi et al, ). This electrocardiographic pattern is commonly seen in anterior localization (83.3%), even though it may sometimes be found in inferior localization (Guo et al, ). Although the underlying mechanisms that are responsible for a tombstone's appearance are unknown, some investigators have suggested that this type of ST‐segment elevation usually occurs due to the presence of multivessel disease with poor collateral circulation and lower LVEF (Balci, ; Guo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Tomb-ST is an electrocardiographic pattern of ST-segment elevation in which the QRS complex, the ST segment, and the T wave merge to form a large upright monophasic deflection called a "tombstone" (Wimalaratna, 1993). Tomb-ST is not an infrequent event; it is detected among 25%-30% of STEMI patients (Guo, Yap, Chen, Huang, & Camm, 2000;Tomcsányi et al, 2005). This electrocardiographic pattern is commonly seen in anterior localization (83.3%), even though it may sometimes be found in inferior localization (Guo et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Several measures of the severity of ischemia in ACO have previously been suggested, such as the Sclarovsky-Birnbaum Ischemia Severity Grading System, (Birnbaum et al, 2014) and the morphology criteria of "tombstoning", presented by Guo et al (Guo, Yap, Chen, Huang, & Camm, 2000). QRS "tombstoning" morphology has been reported to correlate to mortality, in-hospital cardiogenic shock, ventricular tachycardia and ventricular fibrillation, in patients with anterior AMI (Balci, 2009).…”
Section: Discussionmentioning
confidence: 99%